Study Habits in Relation to Socio-Economic Status and Gender among Muslim Adolescents - Ahmad, Nabi; Razia, B (EDUCARE, 2015)
ABSTRACT: Studentsâ educational outcome is greatly influenced by number of factors. Study habits of students and their parental socio-economic status are two such correlates of academic achievement, which have been studied repeatedly during the past five decades. According to D.P. Smith (1961) study, habits included studentâs habits of concentration, note taking, time budgeting, and study method. Research studies indicate that academic achievement of Muslim adolescents in India at secondary level is far behind than their Non-Muslim counter parts and poor academic performance is one of the reasons of school dropouts. The present research is a humble attempt to examine the study habits of Muslim adolescents belonging to different socio-economic strata of the society. The study is descriptive and statistical in nature. Standardized scales have been used to collect the data from a sample of 208 Muslim students. The data was subjected to statistical analysis by applying Mean (M), Standard Deviation (SD), product moment correlation (r), and t-test. Findings of the study indicate that significant difference exists in the study habits of Muslim adolescents in relation to gender, significant and positive relationship exists between study habits and socio-economic status. High SES (Socio-Economic Status) and Low SES Muslim adolescents and similarly Middle SES and Low SES Muslim adolescents differed significantly with regard to their study habits where in both the cases going in favour of the upper SES groups.KEY WORDS: Study habits, socio-economic status, Muslim, adolescents, gender, academic achievement, secondary level, and significant difference exist.Â Â About the Authors: Dr. Nabi Ahmad and B. Razia are Professor and Research Scholar at the Department of Education AMU (Aligarh Muslim University) in Aligarh, Uttar Pradesh, India. For academic purposes, the authors can be contacted via e-mails at: nabiahmad@rediffmail.com and razianaushad.amu@gmail.comHow to cite this article? Ahmad, Nabi & B. Razia. (2015). âStudy Habits in Relation to Socio-Economic Status and Gender among Muslim Adolescentsâ in EDUCARE: International Journal for Educational Studies, Vol.8(1) August, pp.73-80. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Â Chronicle of the article: Accepted (July 6, 2015); Revised (August 6, 2015); and Published (August 25, 2015).